(untitled) (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder of multifactorial etiology involving genetic and environmental factors. This population is more susceptible to develop problems such as dental caries and periodontal disease; however, it is very rare in relation to the involvement of oral cysts and neoplasms. Calcifying odontogenic cyst (COC) is an uncommon lesion, accounting for 1% to 3% of all odontogenic cysts. In most cases, its location is intraosseous, but the peripheral form may be present. Clinically, it presents as asymptomatic swelling and is usually diagnosed on routine radiographs. Due to the low risk of recurrence and favorable prognosis, conservative treatment with local excision through enucleation followed by curettage is recommended. In extensive lesions, methods such as marsupialization or decompression are indicated prior to complete removal in order to preserve adjacent noble structures. The purpose of this paper is to report a COC case in an 18-year-old patient with ASD. The lesion was removed under general anesthesia. The patient has been on follow-up for one year and there is no recurrence. This seems to be the first report in a patient with ASD.